MOTIF KALUAK PAKU SEBAGAI PENCIPTAAN LAMPU HIAS - Panji Satria Rahman; Irwan Irwan (Serupa The Journal of Art Education, 2021)
The making of this final work aims to visualize and express the writer's interest in the form of the kaluak nail motif, through three-dimensional carving as the creation of decorative lights, so that people can learn from minang motifs, one of which is the kaluak nail motif. This work is a description of the writer's anxiety about the lack of knowledge about the role of mamak in Minangkabau. The method used in making this work through several stages, namely: the preparation stage, elaborahi stage, synthesis stage, concept realization stage, and completion stage. So as to produce seven works that visualize the role of mamak in minangkabau with the first title "itself", second "all directions", three "two sides", fourth "graded", fifth "coupling, sixth" embrace "and seventh" lift ".